The Effects of Working Capital Management, Liquidity, Sales Growth and Leverage on Profitability Moderated by Firm Size - Rakhmawati, Ayu; Nalurita, Febria; Hady, Hamdy (Business and Entrepreneurial Review, 2024)
This study aims to the effects of working capital management, liquidity, sales growth, and leverege with size as moderating variable. This study uses desaigned hypothesis testing. Data collection uses secondary data in the form of annual financial reports from IDX consumer goods for five years 2018-2023. The sampling technique used purposive sampling and many as 45 sample companies were obtained with 225 observations. While the data analysis technique used in this study is data panel analysis with e-views 10. The results the research show that there’s effects significant negative working capital management being proxyd with cash conversion cycle toward profitability. Liquidity and leverage does not show significant effect toward profitability. Sales growth has effect significant positive toward profitability. Firm size proved to be moderation and weakened the effect management working capital and leverage significantly toward profitability. Firm size have not proven to be moderation from effect liquidity and sales growth toward profitability at consumer goods companies in Indonesian stock exchange. The implication of this research is that company managers must be able to manage cash efficiently so that production capital can be recovered quickly. Managers must also create effective sales strategies to increase company profits. While before investors invest, it is very necessary to be observant in evaluating financial performance, company liquidity, sales levels and company growth to secure their investments.